Supporting Transmission and Distribution Projects : World Bank Investments since 2010 - Oguah, Samuel; Chattopadhyay, Debabrata; Bazilian, Morgan (World Bank, Washington, DC, 2015)
The World Bank is responding well to its clients’ demand for financing of transmission and distribution projects. By helping to reduce losses, encouraging the integration of renewable energy, and expanding networks to increase supply, supported projects will improve the financial health of utilities, service for consumers, and economic growth. Regional interconnection projects, in particular, are lowering the cost of power, boosting reliability and shrinking the reserve requirements imposed on generation systems. Private sector participation and system wide analysis will be the keys to the success of future projects.